Правовий режим ґрунтів в Україні - Гавриш, Наталя Степанівна; Гавриш, Наталья Степановна; Havrysh, Natalia S. (Одеса, 2018)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.06 – земельне право; аграрне право; екологічне право; природоресурсне право. – Національний університет «Одеська юридична академія», Одеса, 2018. Дисертацію присвячено комплексному та всебічному дослідженню правового режиму ґрунтів в Україні. Робота містить теоретичне узагальнення і нове вирішення наукової проблеми у сфері правового регулювання відносин щодо використання, відтворення та охорони ґрунтів. У дисертації обґрунтовано науково-методологічні основи правового режиму ґрунтів. Розглянуто питання правового режиму ґрунтів у науковій літературі. Визначено ґрунти як об’єкт правового регулювання використання, відтворення та охорони, обґрунтовується теоретико-правова характеристика понять і термінів «земля», «землі», «ґрунти», «ґрунтові ресурси». Визначено юридичні ознаки ґрунтів. Розглянуто нормативно-правові засади використання, відтворення та охорони ґрунтів, методологічні та конституційні основи. Систематизація принципів правової охорони ґрунтів показала, що ґрунти земельних ділянок є об’єктами особливої охорони. В основі такої систематизації лежать принципи міжнародного та європейського права. Установлено особливості правового режиму ґрунтів. Обґрунтовано концепцію раціонального використання ґрунтів як об’єкта земельних, екологічних, аграрних і природоресурсних відносин. Виокремлено особливості правової охорони ґрунтів. Проведено теоретико-правову характеристику ґрунтів як об’єкта правовідносин відтворення. Розкрито специфіку суб’єктного складу правовідносин використання, відтворення та охорони ґрунтів. Охарактеризовано державне регулювання у галузі використання, відтворення та охорони ґрунтів, визначено його поняття, систему та форми. З’ясовано функціонально-правове забезпечення використання, відтворення та охорони ґрунтів. Існуючі організаційно-правові форми та заходи, а також їх функціонально-правове забезпечення дозволило встановити, що в Україні ще не сформовано належних умов відповідно підвищення ефективності правового регулювання використання, відтворення та охорони ґрунтів. Організаційно-правовим способом підвищення ефективності правового регулювання в Україні слід визнати створення Державної служби охорони ґрунтів. Розкрито шляхи вдосконалення правового режиму ґрунтів, проблеми оптимізації законодавства в сфері раціонального використання, відтворення та охорони ґрунтів в Україні.

Диссертация на соискание ученой степени доктора юридических наук по специальности 12.00.06 – земельное право; аграрное право; экологическое право; природоресурсовое право. – Национальный университет «Одесская юридическая академия», Одесса, 2018. Диссертация посвещена комплексному и всестороннему исследованию правового режима почв в Украине. Работа содержит теоретическое обобщение и новое решение научной проблемы в области правового регулирования отношений по использованию, воспроизводству и охране почв. В диссертации обоснованы научно-методологические основы правового режима почв. Рассмотрены вопросы правового режима почв в научной литературе. Определены почвы как объект правового регулирования использования, воспроизводства и охраны, обосновывается теоретико- правовая характеристика понятий и терминов «земля», «земли», «почвы», «почвенные ресурсы». Определено юридические признаки почв. Рассмотрены нормативно-правовые основы использования, воспроизводства и охраны почв, методологические и конституционные основы. Систематизация принципов правовой охраны почв показала, что почвы земельных участков являются объектами особой правовой охраны. В основе такой систематизации лежат принципы международного и европейского права. Установлены особенности правового режима почв. Обосновано концепцию рационального использования почв как объекта земельных, екологических, аграрных и природоресурсовых отношений. Выделены особенности правовой охраны почв. Проведена теоретико-правовая характеристика почв как объекта правоотношений воспроизводства. Раскрыта специфика субъектного состава провоотношений использования, воспроизводства и охраны почв. Охарактеризовано государственное регулирование в области использования, воспроизводства и охраны почв, определено его понятие, система и формы. Выяснено функционально-правовое обеспечение использования, воспроизводства и охраны почв. Существующие организационно-правовые формы и мероприятия, а также их функционально-правовое обеспечение позволило установить, что в Украине еще не сформировано надлежащих условий относительно повышения эффективности правового регулирования использования, воспроизводства и охраны почв. Организационно-правовым способом повышения эффективности правового регулирования в Украине следует признать создание Государственной службы охраны почв. Раскрыты пути усовершенствования правового режима почв, проблемы оптимизации законодательства в области рационального использования, воспроизводства и охраны почв в Украине.

Dissertation for obtaining the degree of Doctor of Law in specialty 12.00.06 – land law; agrarian law; ecological law; natural resource law. – National University «Odessa Law Academy», Odessa, 2018. The dissertation is devoted to the complex and comprehensive study of the legal regime of soils in Ukraine. The work contains a theoretical synthesis and a new solution of the scientific problem in the field of legal regulation of relations concerning the use, reproduction and protection of soils. The scientific and methodological foundations of the legal regime of soils are justified in dissertation. The questions of the legal regime of soils in the scientific literature are considered. Natural and scientific approaches to the concept of “soil”, “soil state” and “soil cover” of Ukraine, which are set out in the special literature and which are generally considered by legal sciences, are studied, but they should be considered as a methodological basis for the development of state policy in this field and formation of legal principles of protection, their rational use and reproduction. It is proposed to establish a legal regime for the use of land areas, which would provide the storage of soil for its use for the main natural purpose. It is concluded that for the basis of the “soil” legal concept it is necessary to take its scientific definition, and in order to improve the mechanism of legal regulation of use, reproduction and protection of soils, it is expedient to predict at the legislative level all the necessary elements of their legal regime. Soils are defined as the object of legal regulation of use, reproduction and protection. It is proposed to single out the soil as an independent object of ecological, land, agrarian and natural resource legal relations with its qualitative property of fertility and as the main and indispensable means of agricultural production. It has been established that the significance of the notion “soil” as the object of legal relations is influenced by the fact that it is a legal category defined by the legislation as having a relation to the land as the main national value, wealth, property rights of the Ukrainian people, the natural component and natural resource. It is proved that the importance of the category “soils” is influenced by the meaning of the term “fertility”, which is used to indicate the characteristics of the soil, and the term “productivity» which is used to indicate the characteristics of the land. The dissertation deals with normative and legal principles of use, reproduction and protection of soils. In this paper the system approach to the consideration of issues of the formation of normative and legal regulation of the use, reproduction and protection of soils, which shows its genesis in Ukraine due to the analysis of legal norms. It is made the conclusion that the existing system of legal norms contained in the current legislation of Ukraine and aimed at regulating of the legal relations of use, reproduction and protection of soils should be codified in the form of the Law of Ukraine “About soils and their fertility”. The principles of use, reproduction and protection of soils are examined. It is noted that today there is no normative legal consolidation of such principles as a combination of public and private interests in land use, priority of the legal regime of agricultural lands, and intensified protection of soils. The expediency of fixing the Law of Ukraine “About the soils and their fertility” of fundamental principles of the system use, restoration and protection of soils. The concept of rational use of soils as an object of land, ecological, agrarian and nature-resource relations is justified. It is established that under the law of the use of soils it is expedient to understand the actions of landowners and land users, regulated by the legislation the field of forestry management, while providing the regime of lands of nature conservation and other nature conservation destination, when exploiting resort, sanative, recreational and other purposes lands. The features of the legal protection of soils are singled out. It is expedient to define the legal protection of soils as a system of legal, organizational, technical, economic and other measures aimed at the restoration of their disturbed state, reproduction, improvement and conservation as an important component of the natural environment, as well as the natural resource which is used in agriculture and forestry as the main means of production. The analysis of scientific positions concerning the interpretation of the concept “especially valuable soils” has been carried out, which testified about differen t methodologica l approache s t o the identification of especially valuable soils. Theoretical and legal characteristics of soils as an object of legal relations of reproduction are conducted. It is noted that the important direction of land protection is the restoration of land, which consists in the implementation of measures aimed at the restoration of the lands lost in the process of agricultural use and under the influence of other anthropogenic actions of the useful qualities of the land as a means of agricultural production and the environmental component (lands reclamation, lands melioration, conservation of lands, fallow). The specifics of the subject structure of legal relationship of the use, reproduction and protection of soil are discovered. It is noted that the land owners and land users, including tenants, users of the subsoil, including public authorities and local self-government, should be recognized as the main subjects of the legal relationship of use, reproduction and protection of soils, which are legally mandated in this area. The author focuses on the state regulation in the field of use, reproduction and protection of soils. The concept, system and forms of state regulation in the field of use, reproduction and protection of soils are analyzed. The expediency of the establishment of the State Service of soil protection, the actions of which will be directed and coordinated by the Cabinet of Ministers of Ukraine through the Minister of Ecology and Natural Resources of Ukraine, is substantiated, this means not only a mechanical exclusion from StateGeoCadastre parts of the control powers in the field of land relations and their transfer to this Service, but a fundamental change of the activity of the state in the field of protection and use of the agricultural fund, which is based on the principle of public-private partnership, and within which the state, by the State Service for soil protection and the agricultural manufacturer, has its own areas of responsibility in ensuring the protection and proper use of agricultural lands. The functional legal support of use, reproduction and protection of soils is determined. It is proved that one of the most important directions for improvement the state of land and soil resources and the stabilization of their ecological status is the improvement of normative and technical support for the use, reproduction and protection of lands and soils. Such organizational legal form is the development and introduction of a system of valuation, standardization and certification in the field of land use and protection of soils. The ways of improvement of the legal regime of soils, problems of optimization of the legislation of rational use, reproduction and protection of soils in Ukraine are discovered. It is stated that the legislation of Ukraine does not properly ensure the special protection of agricultural lands and soils, because the norms of their protection are set out in a non-systematic way and are not sufficiently coordinated with each other. The basic direction of improving the legal and state policy in the field of protection and use of agricultural lands and soils should be program and conceptual documents, the content of which will reflect the functioning of agricultural lands and soil, not only as a means of agricultural production, but also as a natural resource.
дис... д-ра юрид. наук : 12.00.06
Гавриш Н. С. Правовий режим ґрунтів в Україні : дис... д-ра юрид. наук : 12.00.06 / Н. С. Гавриш ; НУ "ОЮА" . - Одеса, 2018. - 437 с.
Keywords: ґрунт; використання ґрунтів; відтворення ґрунтів; правова охорона ґрунтів; земля; землі; ґрунтові ресурси; родючість ґрунтів; псування ґрунтів; забруднення ґрунтів; екологічне право; земельне право; почва; использование почвы; воспроизводство почвы; правовая охрана почвы; земля; земли; почвенные ресурсы; плодородие почвы; порча почвы; загрязнение почвы; экологическое право; земельное право; soil; use of soils; reproduction of soils; soil protection; land; lands; soil resources; soils fertility; soils damage; pollution of soils; ecological law; land law